FORGOTTEN GOITER AFTER TOTAL THYROIDECTOMY: A REPORT OF 07 CASES & LITERATURE REVIEW THORACIC SURGERY DEPARTEMENT'S EXPERIENCE MILITARY HOSPITAL MOHAMMED V OF RABAT - Ihssane KHALEK (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
Introduction: 'Forgotten mediastinal goiter (FMG)'is an extremely rare clinical situation. It consists of discovering, several years after a total thyroidectomy, residual thyroid tissue within the mediastinum, which was overlooked during prior surgery. Few cases were reported and controversy exists regarding the etiology as well as the optimal approach for surgical resection. Material and methods: We conducted a retrospective study based on a series including 07 cases of FMG, observed over 10 years (from January 2010 until December 2020) managed at the Military Hospital Mohammed V of Rabat's Thoracic Surgery Department. We incorporated in our work all the patients who benefited from a 2nd surgery for a forgotten goiter after a previous total thyroidectomy. Our thesis's main purposes are to describe, analyze and evaluate the diagnosis and management strategies, as well as comparing different surgical approaches. Results: 7 patients (3 females and 4 males) with a median age of 45,2 years (range: 32-56 years) presenting a forgotten goiter endured surgery. 2 patients were asymptomatic and 4 patients had dyspnea, 3 patients with chest pain, whereas dysphonia and hyperparathyroidism affected 1 case. None of them had a history of thyroid cancer. The average latency time between the 1A thyroidectomy and re-operation was 3,4 years. The diameter of the masses on CT scan was between 7 and 12 cm in diameter. All the patient underwent sternotomy. Postoperative transitory left recurrent laryngeal nerve palsy was observed in 1 patient. The pathological study objectified multi-hetero-nodular goiter in all cases. Conclusion: FMG should be suspected when postoperative TSH levels remain unchanged. It can be prevented if particular attention is paid to preoperative imaging and per operative management during the 1st procedure. However surgical treatment when performed in specialized centers, is associated with low morbidity.
Keywords: Mediastinal mass; Forgotten goiter; Chest CT; Sternotomy; Mediastinal mass; Forgotten goiter; Chest CT; Sternotomy .